2017
DOI: 10.5937/jrb1707017r
|View full text |Cite
|
Sign up to set email alerts
|

Participation of laypersons in the initiation of cardiopulmonary resuscitation: Why laymen do not help? EuReCa Serbia

Abstract: Sažetak: Cilj:Utvrđivanje uticaja učešća laika, svedoka srčanog zastoja na ishod zbrinjavanja vanbolničkog srčanog zastoja od strane službi hitnih medicinskih pomoći u periodu obuhvaćenim studijom. Metodologija:Podaci o srčanom zastoju prikupljeni su putem jedinstvenog upitnika EuReCa programa u Srbiji tokom realizacije prospektivne, opservacione studije EuReCa One koja je pod brojem NCT02236819 registrovana u bazi trijala i odobrena od zdravstvenih autoriteta u SAD. U istraživanju su uključeni Eureca događaji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
1
0
3
Order By: Relevance
“…Any ROSC rate of 21.0% within the group of OHCA patients with CPR attempt observed in this study is comparable to the ROSC rates reported by most of the previously published investigations [ 2 - 4 , 16 ] However, various findings can be found within the literature regarding rates of shockability of initially detected rhythm with values ranging from 1% to over 50% [ 2 , 3 , 11 ]. The rate observed in this study correlates with previous reports of analysis in the territory of Serbia describing bystander involvement [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Any ROSC rate of 21.0% within the group of OHCA patients with CPR attempt observed in this study is comparable to the ROSC rates reported by most of the previously published investigations [ 2 - 4 , 16 ] However, various findings can be found within the literature regarding rates of shockability of initially detected rhythm with values ranging from 1% to over 50% [ 2 , 3 , 11 ]. The rate observed in this study correlates with previous reports of analysis in the territory of Serbia describing bystander involvement [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Znatna je osvedočenost kolapsu kod vanbolničkog srčanog zastoja u Srbiji naročito kada se ono desi kod kuće, u prebivalištu [11] . Ranija istraživanja ukazuju na razlike u započinjanju mera resuscitacije od strane laika u odnosu na polove [12] .…”
Section: Diskusijaunclassified
“…The importance of the early initiation of basic life support (BLS) measures and early use of automatic external defibrilators (AED) by bystanders before the arrival of the emergency medical service (EMS) units has been extensively explained in the literature, which is also emphasized in the European Resuscitation Council (ERC) guidelines [1][2][3][4][5][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…В помощь практику ющему врачу https://doi.org/10.15360/1813-9779-2021-5-52-64 For Practitioner скорой медицинской помощи (СМП) была подробно описана в литературе, а также подчеркнута в рекомендациях Европейского совета по реанимации (ЕСР) [1][2][3][4][5][14][15][16][17][18][19][20].…”
Section: Introductionunclassified